SCANNING ELECTRON MICROSCOPIC STUDY OF AMNION IN THE MICROCHIROPTERAN BAT, HIPPOSIDEROS SPEORIS AND HUMAN AT FULL TERM PREGNANCY - JAYASHREE TIRPUDE,; POONAM , VERMA SHIVKUMAR (The Bioscan, 2010)
On Scanning Electron Microscopy, at low magnification the single layered amniotic surface appeared to be thrown into folds in (Microcheropteran bat, Hipposideros Speoris Schneider) in near term and polygonal cell gave a mosaic or “cobblestone”appearance was due tot he presence of deep recesses or troughs between adjacent cells. In the intracellular gap openings or “ostia” were common. In human being on SEM four patterns were observed two were the pattern were surrounded by intracellular channels and in other large flat cells observed. The Microvilli in all four pattern, variable morphology in different samples observed. Possible functional implications of the findings are discussed.